2021
DOI: 10.1038/s41416-021-01335-8
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid metabolism is essential for evading physical plasma-induced tumour cell death

Abstract: Background Recent studies have emphasised the important role of amino acids in cancer metabolism. Cold physical plasma is an evolving technology employed to target tumour cells by introducing reactive oxygen species (ROS). However, limited understanding is available on the role of metabolic reprogramming in tumour cells fostering or reducing plasma-induced cancer cell death. Methods The utilisation and impact of major metabolic substrates of fatty acid, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A recent study showed that ovarian cancer cells post ROS exposure did not show any significant alterations in the overall consumption of metabolic substrates across different metabolic pathways. The consumption of metabolic substrates remained more or less similar to that of the cells that were not exposed to ROS [283]. This proves that identifying a proper therapeutic agent that effectively targets ovarian cancer is a difficult task.…”
Section: Conclusion and Future Perspectivementioning
confidence: 63%
“…A recent study showed that ovarian cancer cells post ROS exposure did not show any significant alterations in the overall consumption of metabolic substrates across different metabolic pathways. The consumption of metabolic substrates remained more or less similar to that of the cells that were not exposed to ROS [283]. This proves that identifying a proper therapeutic agent that effectively targets ovarian cancer is a difficult task.…”
Section: Conclusion and Future Perspectivementioning
confidence: 63%
“…The concentration of the ROS can be tuned by changing the ionization variables and the target exposure time [217], while the ambient air condition was found to have a lower impact [218]. As a mechanism of action, gas plasmaderived ROS modulate the expression of redox-regulating enzymes and pathways [219][220][221] and was found to show combinatorial effects with chemotherapy [222][223][224], radiotherapy [225][226][227], and antibody [228] and topical immunotherapy [229]. We have recently also reported for the first time apoptotic effects in patient-derived melanoma tissues [230] and that ROS-derived oxidative posttranslational protein modifications (oxPTMs) generated with gas plasma technology have immunogenic properties and protect from melanoma growth in vivo [231].…”
Section: Cryoablationmentioning
confidence: 99%
“…[ 20–23 ] To this end, there is an effort to understand the main underlying cellular response pathways as this could enable better prediction and improvement of CAP treatment outcome. [ 24–26 ]…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] To this end, there is an effort to understand the main underlying cellular response pathways as this could enable better prediction and improvement of CAP treatment outcome. [24][25][26] For cancer treatment to be long-lasting and efficient for different cancer types, it is often not sufficient that it solely provides cytotoxicity to cancer cells. Namely, cancer cells across and within the tumors are heterogeneous and might respond differently to the same treatment.…”
mentioning
confidence: 99%